A method for preparing a hot pressed insulating film and FFC thereof

By applying a hot-pressed insulating film on FFC cables and using a mixture of mercaptoacrylate and vinyl hydrotalcite-flame retardant compounds with polyester resin and other ingredients, the problem of insufficient flame retardancy of new energy vehicle FFC cables is solved and achieved Provides higher flame retardancy and peel strength.

CN118879225BActive Publication Date: 2025-01-21JIANGSU SIRUIDA NEW MATERIAL TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411389537.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-21
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

While ensuring high peel strength performance, FFC cables on new energy vehicles need higher flame retardancy to ensure safe use.

Method used

Using the preparation method of hot-pressed insulating film, the adhesive is formed by mixing mercaptoacrylate and vinyl hydrotalcite-flame retardant compounds with polyester resin and other ingredients, and cured by a UV curing machine to obtain a high-resistance Insulating film with flammability and peel strength.

Benefits of technology

Improves the flame retardancy and adhesion of FFC, and enhances its stability and safety under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of insulating films, and specifically to a method for preparing a hot-pressed insulating film and its FFC. The present invention uses polyester resin, bisphenol A epoxy resin, acrylic copolymer, flame retardant and other ingredients to prepare a binder. The present invention coats mercaptoacrylate on one surface of a PET film, and then coats a binder on the surface of the side coated with mercaptoacrylate to obtain a hot-pressed insulating film. The hydrotalcite is intercalated and modified using a vinyl polymer to enhance the dispersibility of the hydrotalcite. Then, an efficient flame retardant is prepared using arginine and phosphorous acid, and the vinyl hydrotalcite is compounded with the flame retardant. At this time, the phosphorus-containing flame retardant is intercalated in the hydrotalcite, which better exerts the synergistic effect of the flame retardant and the hydrotalcite, thereby improving the flame retardancy of the insulating film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of insulating films, in particular to a method for preparing a hot-pressed insulating film and a FFC thereof. Background Art

[0002] FFC is a flexible flat cable made of PET and wire as the base material. It has many advantages such as softness, small size, and easy disassembly. Therefore, FFC is widely used in signal transmission and connection of LCD appliances, scanners, fax machines, copiers, audio and other products. With the rapid development of new energy, the application scope of FFC has been further expanded. FFC is further used in new energy vehicles. However, FFC cables on new energy vehicles need higher flame retardancy to ensure safe use while ensuring high peel strength performance.

[0003] In order to solve the above problems and improve the flame retardancy and adhesion of FFC, the present invention provides a hot-pressed insulating film and a method for preparing the FFC. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a hot pressed insulating film and a FFC thereof, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A method for preparing a hot-pressed insulating film comprises the following steps:

[0007] Step 1: Take a flame retardant and vinyl hydrotalcite, stir at 115-120° C. for 3-4 hours, filter, dry and grind to obtain a vinyl hydrotalcite-flame retardant composite;

[0008] Step 2: Take polyester resin, bisphenol A epoxy resin, acrylic copolymer, 2,2-dimethoxy-2-phenylacetophenone, vinyl hydrotalcite-flame retardant composite, antioxidant 1010, bismuth isooctanoate, and butanone and mix them evenly to obtain a binder;

[0009] Step 3: coating mercaptoacrylate on one surface of the PET film, then coating the adhesive on the surface coated with mercaptoacrylate, irradiating with a UV curing machine for 50-60 seconds, and drying to obtain an insulating film.

[0010] More optimally, the binder includes the following ingredients, by weight: 80-100 parts of polyester resin, 10-15 parts of bisphenol A epoxy resin, 5-10 parts of acrylic copolymer, 0.06-0.1 parts of 2,2-dimethoxy-2-phenylacetophenone, 60-70 parts of vinyl hydrotalcite-flame retardant composite, 0.5-1 parts of antioxidant 1010, 0.05-0.1 parts of bismuth isooctanoate, and 75-100 parts of butanone.

[0011] More optimally, the preparation method of the vinyl hydrotalcite is: take methacrylic acid, itaconic acid, ammonium persulfate, and sodium bisulfite, stir at 75-80°C for 6-7h to obtain a vinyl polymer; take hydrotalcite and deionized water, stir evenly, add the vinyl polymer, stir at 80-85°C for 5-6h, centrifuge, and dry to obtain the vinyl hydrotalcite.

[0012] More optimally, the preparation method of the hydrotalcite is: take anhydrous sodium carbonate and deionized water, stir evenly to obtain a sodium carbonate aqueous solution; take sodium hydroxide and deionized water, stir evenly to obtain a sodium hydroxide solution; take aluminum nitrate nonahydrate, magnesium nitrate hexahydrate, zirconium nitrate pentahydrate, and deionized water, stir evenly to obtain a metal salt solution; add the metal salt solution dropwise to the sodium carbonate aqueous solution, then add sodium hydroxide solution dropwise to adjust the pH value to 11-12, stir at 80-85°C for 5-7h, centrifuge, dry, and grind to obtain hydrotalcite.

[0013] More optimally, the preparation method of the flame retardant is: take arginine, phosphorous acid, and deionized water, stir evenly, add formaldehyde solution dropwise, heat to 100°C, reflux for 2-4h, cool to 25-35°C, add urea, heat to 125-130°C and react for 2-3h to obtain the flame retardant.

[0014] Preferably, the preparation method of the mercaptoacrylate comprises the following steps:

[0015] S1: Take phosphorus oxychloride and ether, stir evenly to obtain a phosphorus oxychloride mixed solution; take triethylamine, hydroxyethyl acrylate, and ether, stir evenly, then dropwise add the phosphorus oxychloride mixed solution in an ice bath, react for 10-12 hours, filter, wash, take the organic phase, dry, and rotary evaporate to obtain compound A;

[0016] S2: Compound A and pentaerythritol tetrakis(3-mercaptopropionic acid) ester are mixed evenly, and a photoinitiator 2,2-dimethoxy-2-phenylacetophenone is added and mixed evenly to obtain mercapto acrylate.

[0017] A hot pressed insulating film is prepared by a method for preparing a hot pressed insulating film.

[0018] A FFC comprises a conducting wire and an insulating film covering both sides of the upper and lower surfaces of the conducting wire.

[0019] A method for preparing an FFC comprises the following steps: placing an insulating film on the upper surface and the lower surface of a conductor respectively, laminating the side of the insulating film coated with an adhesive to the pure copper conductor, rolling and light curing at 175-180°C, and baking at 120-125°C to obtain the FFC.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] (1) The present invention prepares a mercaptoacrylate and adds phosphorus oxychloride thereto, so that the mercaptoacrylate contains a phosphate functional group, which generates polyphosphoric acid compounds during thermal degradation and plays a role in catalyzing the dehydration and carbonization of macromolecular chains. When the polyphosphoric acid compounds are coated on an insulating film, they can play a good flame retardant role.

[0022] (2) The present invention uses vinyl polymer to perform intercalation modification on hydrotalcite, thereby enhancing the dispersibility of hydrotalcite. Then, a high-efficiency flame retardant is prepared using arginine and phosphorous acid, and the vinyl hydrotalcite is compounded with the flame retardant. At this time, the phosphorus-containing flame retardant is intercalated in the hydrotalcite, which better exerts the synergistic effect of the flame retardant and the hydrotalcite, thereby improving the flame retardancy of the insulating film.

[0023] (3) The present invention prepares an adhesive using polyester resin, bisphenol A epoxy resin, acrylic copolymer, flame retardant and other ingredients. Mercaptoacrylate is coated on one surface of the PET film, and then the adhesive is coated on the surface of the side coated with mercaptoacrylate to obtain a hot-pressed insulating film. At this time, the vinyl group in the vinyl hydrotalcite-flame retardant composite can react with the mercapto group in the mercaptoacrylate to enhance the peel strength of the FFC. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] The raw materials involved in the present invention are not particularly limited in terms of manufacturer and model, and exemplary include: polyester resin: can be purchased from Eastman, model: CG933; bisphenol A type epoxy resin: model: E44; acrylic copolymer: can be purchased from Arkema, France, model: 3125; PET film: thickness 38µm, purchased from Sichuan Dongcai.

[0026] Embodiment 1: A method for preparing a hot-pressed insulating film, comprising the following steps:

[0027] Step 1: Preparation of mercaptoacrylate:

[0028] Take 15 g of phosphorus oxychloride and 20 mL of ether, stir evenly to obtain a phosphorus oxychloride mixed solution; take 34 g of triethylamine, 35 g of hydroxyethyl acrylate, and 100 mL of ether, stir evenly, then dropwise add the phosphorus oxychloride mixed solution in an ice bath, react at 0°C for 11 hours, filter, wash, take the organic phase, dry, and rotary evaporate to obtain compound A;

[0029] Take 7g of compound A and 14g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester, mix them evenly, add 0.42g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone, mix them evenly, and obtain mercapto acrylate;

[0030] Step 2: Preparation of flame retardant:

[0031] Take 9g of arginine, 25g of phosphorous acid, and 20mL of deionized water, stir evenly, add 25g of 37% formaldehyde solution, heat to 100°C, reflux for 3h, cool to 30°C, add 5.3g of urea, heat to 127°C and react for 2.5h to obtain a flame retardant;

[0032] Step 3: Preparation of vinyl hydrotalcite:

[0033] S1: Take 10g of anhydrous sodium carbonate and 100mL of deionized water, stir evenly to obtain a sodium carbonate aqueous solution; take 8g of sodium hydroxide and 100mL of deionized water, stir evenly to obtain a sodium hydroxide solution; take 8g of aluminum nitrate nonahydrate, 15g of magnesium nitrate hexahydrate, 5g of zirconium nitrate pentahydrate, and 100mL of deionized water, stir evenly to obtain a metal salt solution; add the metal salt solution dropwise to the sodium carbonate aqueous solution, then add sodium hydroxide solution dropwise to adjust the pH value to 11.5, stir at 83°C for 6h, centrifuge, dry, and grind to obtain hydrotalcite;

[0034] S2: 24 g of methacrylic acid, 12 g of itaconic acid, 0.5 g of ammonium persulfate, and 0.1 g of sodium bisulfite were stirred at 77 °C for 6.5 h to obtain a vinyl polymer;

[0035] S3: Take 2 g of hydrotalcite and 100 mL of deionized water, stir evenly, add 4 g of vinyl polymer, stir at 83 ° C for 5.5 h, centrifuge and dry to obtain vinyl hydrotalcite;

[0036] Step 4: Preparation of vinyl hydrotalcite-flame retardant composite:

[0037] Take 3 g of flame retardant and 0.7 g of vinyl hydrotalcite, stir at 118° C. for 3.5 h, filter, dry and grind to obtain a vinyl hydrotalcite-flame retardant composite;

[0038] Step 5: Preparation of hot pressed insulating film:

[0039] Mix polyester resin, bisphenol A epoxy resin, acrylic copolymer, pentaerythritol tetrakis(3-mercaptopropionate), vinyl hydrotalcite-flame retardant composite, antioxidant 1010, bismuth isooctanoate and butanone to obtain a binder;

[0040] The binder comprises the following components, by weight: 90 parts of polyester resin, 12 parts of bisphenol A epoxy resin, 7 parts of acrylic copolymer, 0.07 parts of 2,2-dimethoxy-2-phenylacetophenone, 65 parts of vinyl hydrotalcite-flame retardant composite, 0.7 parts of antioxidant 1010, 0.07 parts of bismuth isooctanoate, and 85 parts of butanone;

[0041] The PET film is coated with mercaptoacrylate on one side thereof, with a coating thickness of 10 μm; then, an adhesive is coated on the side coated with mercaptoacrylate, with an adhesive coating thickness of 15 μm; an ultraviolet curing machine is used for irradiation for 55 seconds, and the film is dried to obtain a hot-pressed insulating film;

[0042] A hot-pressed insulating film is placed on the upper and lower surfaces of eight pure copper wires with a line spacing of 2.0 mm, so that the side of the hot-pressed insulating film coated with an adhesive is bonded to the pure copper wire, rolled and light-cured at 177°C, and baked at 122°C to obtain FFC.

[0043] Embodiment 2: A method for preparing a hot-pressed insulating film, comprising the following steps:

[0044] Step 1: Preparation of mercaptoacrylate:

[0045] Take 15g of phosphorus oxychloride and 20mL of ether, stir evenly to obtain a phosphorus oxychloride mixed solution; take 34g of triethylamine, 35g of hydroxyethyl acrylate, and 100mL of ether, stir evenly, then dropwise add the phosphorus oxychloride mixed solution in an ice bath, react at 0°C for 10h, filter, wash, take the organic phase, dry, and rotary evaporate to obtain compound A;

[0046] Take 7g of compound A and 14g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester, mix them evenly, add 0.42g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone, mix them evenly, and obtain mercapto acrylate;

[0047] Step 2: Preparation of flame retardant:

[0048] Take 9g of arginine, 25g of phosphorous acid, and 20mL of deionized water, stir evenly, add 25g of 37% formaldehyde solution dropwise, heat to 100°C, reflux for 2h, cool to 25°C, add 5.3g of urea, heat to 125°C and react for 3h to obtain a flame retardant;

[0049] Step 3: Preparation of vinyl hydrotalcite:

[0050] S1: Take 10g of anhydrous sodium carbonate and 100mL of deionized water, stir evenly to obtain a sodium carbonate aqueous solution; take 8g of sodium hydroxide and 100mL of deionized water, stir evenly to obtain a sodium hydroxide solution; take 8g of aluminum nitrate nonahydrate, 15g of magnesium nitrate hexahydrate, 5g of zirconium nitrate pentahydrate, and 100mL of deionized water, stir evenly to obtain a metal salt solution; add the metal salt solution dropwise to the sodium carbonate aqueous solution, then add the sodium hydroxide solution dropwise to adjust the pH value to 11, stir at 80°C for 5h, centrifuge, dry, and grind to obtain hydrotalcite;

[0051] S2: Take 24 g of methacrylic acid, 12 g of itaconic acid, 0.5 g of ammonium persulfate, and 0.1 g of sodium bisulfite, and stir at 75 °C for 6 h to obtain a vinyl polymer;

[0052] S3: Take 2 g of hydrotalcite and 100 mL of deionized water, stir evenly, add 4 g of vinyl polymer, stir at 80 ° C for 5 h, centrifuge and dry to obtain vinyl hydrotalcite;

[0053] Step 4: Preparation of vinyl hydrotalcite-flame retardant composite:

[0054] Take 3 g of flame retardant and 0.7 g of vinyl hydrotalcite, stir at 115° C. for 3 h, filter, dry and grind to obtain a vinyl hydrotalcite-flame retardant composite;

[0055] Step 5: Preparation of hot pressed insulating film:

[0056] Mix polyester resin, bisphenol A epoxy resin, acrylic copolymer, pentaerythritol tetrakis(3-mercaptopropionate), vinyl hydrotalcite-flame retardant composite, antioxidant 1010, bismuth isooctanoate and butanone to obtain a binder;

[0057] The binder comprises the following components, by weight: 80 parts of polyester resin, 10 parts of bisphenol A epoxy resin, 5 parts of acrylic copolymer, 0.06 parts of 2,2-dimethoxy-2-phenylacetophenone, 60 parts of vinyl hydrotalcite-flame retardant composite, 0.5 parts of antioxidant 1010, 0.05 parts of bismuth isooctanoate, and 75 parts of butanone;

[0058] The mercaptoacrylate is coated on one side of the PET film, and the coating thickness is 10µm; then the adhesive is coated on the side coated with the mercaptoacrylate, and the adhesive coating thickness is 15µm; an ultraviolet curing machine is used to irradiate for 50s, and dried to obtain a hot-pressed insulating film;

[0059] A hot-pressed insulating film is placed on the upper and lower surfaces of eight pure copper wires with a line spacing of 2.0 mm, so that the side of the hot-pressed insulating film coated with an adhesive is bonded to the pure copper wire, rolled and light-cured at 175°C, and baked at 120°C to obtain FFC.

[0060] Embodiment 3: A method for preparing a hot-pressed insulating film, comprising the following steps:

[0061] Step 1: Preparation of mercaptoacrylate:

[0062] Take 15 g of phosphorus oxychloride and 20 mL of ether, stir evenly to obtain a phosphorus oxychloride mixed solution; take 34 g of triethylamine, 35 g of hydroxyethyl acrylate, and 100 mL of ether, stir evenly, then dropwise add the phosphorus oxychloride mixed solution in an ice bath, react at 0°C for 12 h, filter, wash, take the organic phase, dry, and rotary evaporate to obtain compound A;

[0063] Take 7g of compound A and 14g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester, mix them evenly, add 0.42g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone, mix them evenly, and obtain mercapto acrylate;

[0064] Step 2: Preparation of flame retardant:

[0065] Take 9g of arginine, 25g of phosphorous acid, and 20mL of deionized water, stir evenly, add 25g of 37% formaldehyde solution dropwise, heat to 100°C, reflux for 4h, cool to 35°C, add 5.3g of urea, heat to 130°C and react for 2h to obtain a flame retardant;

[0066] Step 3: Preparation of vinyl hydrotalcite:

[0067] S1: Take 10g of anhydrous sodium carbonate and 100mL of deionized water, stir evenly to obtain a sodium carbonate aqueous solution; take 8g of sodium hydroxide and 100mL of deionized water, stir evenly to obtain a sodium hydroxide solution; take 8g of aluminum nitrate nonahydrate, 15g of magnesium nitrate hexahydrate, 5g of zirconium nitrate pentahydrate, and 100mL of deionized water, stir evenly to obtain a metal salt solution; add the metal salt solution dropwise to the sodium carbonate aqueous solution, then add the sodium hydroxide solution dropwise to adjust the pH value to 12, stir at 85°C for 7h, centrifuge, dry, and grind to obtain hydrotalcite;

[0068] S2: Take 24 g of methacrylic acid, 12 g of itaconic acid, 0.5 g of ammonium persulfate, and 0.1 g of sodium bisulfite, and stir at 80°C for 7 h to obtain a vinyl polymer;

[0069] S3: Take 2 g of hydrotalcite and 100 mL of deionized water, stir evenly, add 4 g of vinyl polymer, stir at 85 ° C for 6 h, centrifuge and dry to obtain vinyl hydrotalcite;

[0070] Step 4: Preparation of vinyl hydrotalcite-flame retardant composite:

[0071] Take 3 g of flame retardant and 0.7 g of vinyl hydrotalcite, stir at 120° C. for 4 h, filter, dry and grind to obtain a vinyl hydrotalcite-flame retardant composite;

[0072] Step 5: Preparation of hot pressed insulating film:

[0073] Mix polyester resin, bisphenol A epoxy resin, acrylic copolymer, pentaerythritol tetrakis(3-mercaptopropionate), vinyl hydrotalcite-flame retardant composite, antioxidant 1010, bismuth isooctanoate and butanone to obtain a binder;

[0074] The binder comprises the following components, by weight: 100 parts of polyester resin, 15 parts of bisphenol A epoxy resin, 10 parts of acrylic copolymer, 0.1 parts of 2,2-dimethoxy-2-phenylacetophenone, 70 parts of vinyl hydrotalcite-flame retardant composite, 1 part of antioxidant 1010, 0.1 parts of bismuth isooctanoate, and 100 parts of butanone;

[0075] The mercaptoacrylate is coated on one side of the PET film, and the coating thickness is 10µm; then the adhesive is coated on the side coated with the mercaptoacrylate, and the adhesive coating thickness is 15µm; an ultraviolet curing machine is used to irradiate for 60s, and dried to obtain a hot-pressed insulating film;

[0076] A hot-pressed insulating film is placed on the upper and lower surfaces of eight pure copper wires with a line spacing of 2.0 mm, so that the side of the hot-pressed insulating film coated with an adhesive is bonded to the pure copper wire, rolled and light-cured at 180°C, and baked at 125°C to obtain FFC.

[0077] Comparative Example 1: mercaptoacrylate was not applied, and the rest was the same as Example 1:

[0078] Step 1: Preparation of flame retardant:

[0079] Take 9g of arginine, 25g of phosphorous acid, and 20mL of deionized water, stir evenly, add 25g of 37% formaldehyde solution, heat to 100°C, reflux for 3h, cool to 30°C, add 5.3g of urea, heat to 127°C and react for 2.5h to obtain a flame retardant;

[0080] Step 2: Preparation of vinyl hydrotalcite:

[0081] S1: Take 10g of anhydrous sodium carbonate and 100mL of deionized water, stir evenly to obtain a sodium carbonate aqueous solution; take 8g of sodium hydroxide and 100mL of deionized water, stir evenly to obtain a sodium hydroxide solution; take 8g of aluminum nitrate nonahydrate, 15g of magnesium nitrate hexahydrate, 5g of zirconium nitrate pentahydrate, and 100mL of deionized water, stir evenly to obtain a metal salt solution; add the metal salt solution dropwise to the sodium carbonate aqueous solution, then add sodium hydroxide solution dropwise to adjust the pH value to 11.5, stir at 83°C for 6h, centrifuge, dry, and grind to obtain hydrotalcite;

[0082] S2: 24 g of methacrylic acid, 12 g of itaconic acid, 0.5 g of ammonium persulfate, and 0.1 g of sodium bisulfite were stirred at 77 °C for 6.5 h to obtain a vinyl polymer;

[0083] S3: Take 2 g of hydrotalcite and 100 mL of deionized water, stir evenly, add 4 g of vinyl polymer, stir at 83 ° C for 5.5 h, centrifuge and dry to obtain vinyl hydrotalcite;

[0084] Step 3: Preparation of vinyl hydrotalcite-flame retardant composite:

[0085] Take 3 g of flame retardant and 0.7 g of vinyl hydrotalcite, stir at 118° C. for 3.5 h, filter, dry and grind to obtain a vinyl hydrotalcite-flame retardant composite;

[0086] Step 4: Preparation of hot pressed insulating film:

[0087] Mix polyester resin, bisphenol A epoxy resin, acrylic copolymer, pentaerythritol tetrakis(3-mercaptopropionate), vinyl hydrotalcite-flame retardant composite, antioxidant 1010, bismuth isooctanoate and butanone to obtain a binder;

[0088] The binder comprises the following components, by weight: 90 parts of polyester resin, 12 parts of bisphenol A epoxy resin, 7 parts of acrylic copolymer, 0.07 parts of 2,2-dimethoxy-2-phenylacetophenone, 65 parts of vinyl hydrotalcite-flame retardant composite, 0.7 parts of antioxidant 1010, 0.07 parts of bismuth isooctanoate, and 85 parts of butanone;

[0089] The adhesive is coated on one side of the PET film, and the thickness of the adhesive coating is 25 µm; an ultraviolet curing machine is used for irradiation for 55 seconds, and the film is dried to obtain a hot-pressed insulating film;

[0090] A hot-pressed insulating film is placed on the upper and lower surfaces of eight pure copper wires with a line spacing of 2.0 mm, so that the side of the hot-pressed insulating film coated with an adhesive is bonded to the pure copper wire, rolled and light-cured at 177°C, and baked at 122°C to obtain FFC.

[0091] Comparative Example 2: The hydrotalcite is not vinyl-modified, and the rest is the same as Example 1:

[0092] Step 1: Preparation of mercaptoacrylate:

[0093] Take 15 g of phosphorus oxychloride and 20 mL of ether, stir evenly to obtain a phosphorus oxychloride mixed solution; take 34 g of triethylamine, 35 g of hydroxyethyl acrylate, and 100 mL of ether, stir evenly, then dropwise add the phosphorus oxychloride mixed solution in an ice bath, react at 0°C for 11 hours, filter, wash, take the organic phase, dry, and rotary evaporate to obtain compound A;

[0094] Take 7g of compound A and 14g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester, mix them evenly, add 0.42g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone, mix them evenly, and obtain mercapto acrylate;

[0095] Step 2: Preparation of flame retardant:

[0096] Take 9g of arginine, 25g of phosphorous acid, and 20mL of deionized water, stir evenly, add 25g of 37% formaldehyde solution, heat to 100°C, reflux for 3h, cool to 30°C, add 5.3g of urea, heat to 127°C and react for 2.5h to obtain a flame retardant;

[0097] Step 3: Preparation of hydrotalcite:

[0098] Take 10g of anhydrous sodium carbonate and 100mL of deionized water, stir evenly to obtain a sodium carbonate aqueous solution; take 8g of sodium hydroxide and 100mL of deionized water, stir evenly to obtain a sodium hydroxide solution; take 8g of aluminum nitrate nonahydrate, 15g of magnesium nitrate hexahydrate, 5g of zirconium nitrate pentahydrate, and 100mL of deionized water, stir evenly to obtain a metal salt solution; add the metal salt solution dropwise to the sodium carbonate aqueous solution, then add the sodium hydroxide solution dropwise to adjust the pH value to 11.5, stir at 83°C for 6h, centrifuge, dry, and grind to obtain hydrotalcite;

[0099] Step 4: Preparation of hydrotalcite-flame retardant composite:

[0100] Take 3 g of flame retardant and 0.7 g of hydrotalcite, stir at 118° C. for 3.5 h, filter, dry and grind to obtain a hydrotalcite-flame retardant composite;

[0101] Step 5: Preparation of hot pressed insulating film:

[0102] Mix polyester resin, bisphenol A epoxy resin, acrylic copolymer, pentaerythritol tetrakis(3-mercaptopropionate), hydrotalcite-flame retardant composite, antioxidant 1010, bismuth isooctanoate and butanone to obtain a binder;

[0103] The binder comprises the following components, by weight: 90 parts of polyester resin, 12 parts of bisphenol A epoxy resin, 7 parts of acrylic copolymer, 0.07 parts of 2,2-dimethoxy-2-phenylacetophenone, 65 parts of hydrotalcite-flame retardant composite, 0.7 parts of antioxidant 1010, 0.07 parts of bismuth isooctanoate, and 85 parts of butanone;

[0104] The PET film is coated with mercaptoacrylate on one side thereof, with a coating thickness of 10 μm; then, an adhesive is coated on the side coated with mercaptoacrylate, with an adhesive coating thickness of 15 μm; an ultraviolet curing machine is used for irradiation for 55 seconds, and the film is dried to obtain a hot-pressed insulating film;

[0105] A hot-pressed insulating film is placed on the upper and lower surfaces of eight pure copper wires with a line spacing of 2.0 mm, so that the side of the hot-pressed insulating film coated with an adhesive is bonded to the pure copper wire, rolled and light-cured at 177°C, and baked at 122°C to obtain FFC.

[0106] Comparative Example 3: The flame retardant and hydrotalcite are not compounded, and the rest is the same as Example 1:

[0107] Step 1: Preparation of mercaptoacrylate:

[0108] Take 15 g of phosphorus oxychloride and 20 mL of ether, stir evenly to obtain a phosphorus oxychloride mixed solution; take 34 g of triethylamine, 35 g of hydroxyethyl acrylate, and 100 mL of ether, stir evenly, then dropwise add the phosphorus oxychloride mixed solution in an ice bath, react at 0°C for 11 hours, filter, wash, take the organic phase, dry, and rotary evaporate to obtain compound A;

[0109] Take 7g of compound A and 14g of pentaerythritol tetrakis(3-mercaptopropionic acid) ester, mix them evenly, add 0.42g of photoinitiator 2,2-dimethoxy-2-phenylacetophenone, mix them evenly, and obtain mercapto acrylate;

[0110] Step 2: Preparation of flame retardant:

[0111] Take 9g of arginine, 25g of phosphorous acid, and 20mL of deionized water, stir evenly, add 25g of 37% formaldehyde solution, heat to 100°C, reflux for 3h, cool to 30°C, add 5.3g of urea, heat to 127°C and react for 2.5h to obtain a flame retardant;

[0112] Step 3: Preparation of vinyl hydrotalcite:

[0113] S1: Take 10g of anhydrous sodium carbonate and 100mL of deionized water, stir evenly to obtain a sodium carbonate aqueous solution; take 8g of sodium hydroxide and 100mL of deionized water, stir evenly to obtain a sodium hydroxide solution; take 8g of aluminum nitrate nonahydrate, 15g of magnesium nitrate hexahydrate, 5g of zirconium nitrate pentahydrate, and 100mL of deionized water, stir evenly to obtain a metal salt solution; add the metal salt solution dropwise to the sodium carbonate aqueous solution, then add sodium hydroxide solution dropwise to adjust the pH value to 11.5, stir at 83°C for 6h, centrifuge, dry, and grind to obtain hydrotalcite;

[0114] S2: 24 g of methacrylic acid, 12 g of itaconic acid, 0.5 g of ammonium persulfate, and 0.1 g of sodium bisulfite were stirred at 77 °C for 6.5 h to obtain a vinyl polymer;

[0115] S3: Take 2 g of hydrotalcite and 100 mL of deionized water, stir evenly, add 4 g of vinyl polymer, stir at 83 ° C for 5.5 h, centrifuge and dry to obtain vinyl hydrotalcite;

[0116] Step 4: Preparation of hot pressed insulating film:

[0117] Mix polyester resin, bisphenol A epoxy resin, acrylic copolymer, pentaerythritol tetrakis(3-mercaptopropionate), vinyl hydrotalcite, flame retardant, antioxidant 1010, bismuth isooctanoate and butanone to obtain a binder;

[0118] The binder comprises the following components, by weight: 90 parts of polyester resin, 12 parts of bisphenol A epoxy resin, 7 parts of acrylic copolymer, 0.07 parts of 2,2-dimethoxy-2-phenylacetophenone, 50 parts of vinyl hydrotalcite, 15 parts of flame retardant, 0.7 parts of antioxidant 1010, 0.07 parts of bismuth isooctanoate, and 85 parts of butanone;

[0119] The PET film is coated with mercaptoacrylate on one side thereof, with a coating thickness of 10 μm; then, an adhesive is coated on the side coated with mercaptoacrylate, with an adhesive coating thickness of 15 μm; an ultraviolet curing machine is used for irradiation for 55 seconds, and the film is dried to obtain a hot-pressed insulating film;

[0120] A hot-pressed insulating film is placed on the upper and lower surfaces of eight pure copper wires with a line spacing of 2.0 mm, so that the side of the hot-pressed insulating film coated with an adhesive is bonded to the pure copper wire, rolled and light-cured at 177°C, and baked at 122°C to obtain FFC.

[0121] experiment:

[0122] The FFC prepared by Example 1-3 and Comparative Example 1-3 was subjected to a peel strength test at 180° and a speed of 100 mm / min. The insulating film prepared by Example 1-3 and Comparative Example 1-3 was cut into 50 mm×200 mm specimens for flame retardancy test. The flame retardancy grades of the films were classified with reference to UL-94, with the highest flame retardancy grade being VTM-0, followed by VTM-1, VTM-2, HB, etc. The insulating film was subjected to a limiting oxygen index test, and the obtained data were shown in the following table:

[0123]

[0124] Conclusion: From the comparison of the data in the table, it can be seen that in Comparative Example 1, mercaptoacrylate is not coated, the peel strength of FFC decreases, and the flame retardancy deteriorates. In Comparative Example 2, hydrotalcite is not vinyl-modified, the dispersibility of hydrotalcite deteriorates, and the hydrotalcite-flame retardant composite cannot react with the thiol group in mercaptoacrylate, and the peel strength of FFC deteriorates. In Comparative Example 3, the flame retardant and hydrotalcite are not compounded, and the flame retardant performance decreases. Examples 1-3 use vinyl polymers to intercalate and modify hydrotalcite, which enhances the dispersibility of hydrotalcite. Then, a high-efficiency flame retardant is prepared using arginine and phosphorous acid, and the vinyl hydrotalcite is compounded with the flame retardant. At this time, the phosphorus-containing flame retardant is intercalated in the hydrotalcite, which better exerts the synergistic effect of the flame retardant and the hydrotalcite, and improves the flame retardancy of the insulating film. The vinyl group in the vinyl hydrotalcite-flame retardant composite can react with the thiol group in the mercaptoacrylate, which enhances the peel strength of FFC.

[0125] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a hot pressed insulating film, characterized in that: The following steps are involved: Step 1: Take a flame retardant and vinyl hydrotalcite, stir at 115-120° C. for 3-4 hours, filter, dry and grind to obtain a vinyl hydrotalcite-flame retardant composite; Step 2: Take polyester resin, bisphenol A epoxy resin, acrylic copolymer, 2,2-dimethoxy-2-phenylacetophenone, vinyl hydrotalcite-flame retardant composite, antioxidant 1010, bismuth isooctanoate, and butanone and mix them evenly to obtain a binder; Step 3: coating mercaptoacrylate on one side of the PET film, then coating the adhesive on the side coated with mercaptoacrylate, irradiating with a UV curing machine for 50-60 seconds, and drying to obtain an insulating film; The binder comprises the following components, by weight: 80-100 parts of polyester resin, 10-15 parts of bisphenol A epoxy resin, 5-10 parts of acrylic copolymer, 0.06-0.1 parts of 2,2-dimethoxy-2-phenylacetophenone, 60-70 parts of vinyl hydrotalcite-flame retardant composite, 0.5-1 parts of antioxidant 1010, 0.05-0.1 parts of bismuth isooctanoate, and 75-100 parts of butanone; Take methacrylic acid, itaconic acid, ammonium persulfate, and sodium bisulfite, stir at 75-80°C for 6-7 hours to obtain a vinyl polymer; take hydrotalcite and deionized water, stir evenly, add the vinyl polymer, stir at 80-85°C for 5-6 hours, centrifuge, and dry to obtain vinyl hydrotalcite; The flame retardant is prepared by: taking arginine, phosphorous acid and deionized water, stirring evenly, adding formaldehyde solution dropwise, heating to 100° C., reflux for 2-4 hours, cooling to 25-35° C., adding urea, heating to 125-130° C. and reacting for 2-3 hours to obtain the flame retardant; The preparation method of the mercaptoacrylate is: The following steps are involved: S1: Take phosphorus oxychloride and ether, stir evenly to obtain a phosphorus oxychloride mixed solution; take triethylamine, hydroxyethyl acrylate, and ether, stir evenly, then dropwise add the phosphorus oxychloride mixed solution in an ice bath, react for 10-12 hours, filter, wash, take the organic phase, dry, and rotary evaporate to obtain compound A; S2: Compound A and pentaerythritol tetrakis(3-mercaptopropionic acid) ester are mixed evenly, and a photoinitiator 2,2-dimethoxy-2-phenylacetophenone is added and mixed evenly to obtain mercapto acrylate.

2. The method for preparing a hot-pressed insulating film according to claim 1, characterized in that: The preparation method of the hydrotalcite comprises the following steps: taking anhydrous sodium carbonate and deionized water, stirring evenly to obtain a sodium carbonate aqueous solution; taking sodium hydroxide and deionized water, stirring evenly to obtain a sodium hydroxide solution; taking aluminum nitrate nonahydrate, magnesium nitrate hexahydrate, zirconium nitrate pentahydrate and deionized water, stirring evenly to obtain a metal salt solution; dropping the metal salt solution into the sodium carbonate aqueous solution, then dropping the sodium hydroxide solution to adjust the pH value to 11-12, stirring at 80-85° C. for 5-7 hours, centrifuging, drying and grinding to obtain the hydrotalcite.

3. A hot-pressed insulating film prepared according to the method for preparing a hot-pressed insulating film according to any one of claims 1 to 2.

4. An FFC, characterized in that: The FFC comprises a conductive line and the insulating film as claimed in claim 3 covering both upper and lower surfaces of the conductive line.

5. A method for preparing FFC, characterized in that: The following steps are involved: An insulating film as claimed in claim 3 is placed on the upper and lower surfaces of the conductor respectively, so that the side of the insulating film coated with the adhesive is bonded to the pure copper conductor, rolled and light-cured at 175-180°C, and baked at 120-125°C to obtain FFC.

Citation Information

Patent Citations

  • Flexible flat cable

    CN102201277A

  • Hydrotalcite / phosphorus nitrogen series flame retardant compounded flame-retarding PET (Polyethylene Terephthalate) material and preparation method thereof

    CN108084472A